Static parameter estimation and testability analysis of distribution lines based on multi-source measurement information - Chen, Lupeng; Liu, Jian; Pan, Zhongmei; Zhang, Zhihua (Frontiers in Energy Research, 2023)
The information monitoring of distribution networks usually relies on multiple measurement systems, and the placement and number of measurement configurations are also restricted by objective factors. It is highly likely that insufficient measurements will affect the parameter estimation of distribution lines. To deal with the aforementioned issue, this paper establishes the measurement equations for static parameters of distribution lines and proposes a method of parameter estimation based on the elitist searching approach. Aiming at different measurement conditions, the testability analysis method is introduced to distinguish clear parameters and uncertain parameters of distribution lines. For the constructed line parameter samples, the estimated values of line parameters are calculated with the consideration of multi-source effective measurement data at different time points. Moreover, the indices of relative errors between the sample values and the estimated values are used to judge the testability of static parameters of distribution lines. The case study on IEEE 33 bus distribution system analyzes the application scenarios with and without measurement errors. The simulation results show that the testability analysis method can effectively identify whether the parameters to be estimated are clear or not, and then the estimated values of clear parameters and the bounds of some disturbing uncertain parameters can be estimated accurately to provide certain decision support for engineering applications.